Angiosarcoma on Top of a Meningioma Mimicking a Transosseous Meningioma: an Interdisciplinary Point of View - Kohl, Jana; König, Rebecca E; Kraus, Armin; Mawrin, Christian; Paukisch, Harald; Stein, Klaus-Peter; Rashidi, Ali; Luchtmann, Michael; Sandalcioglu, I Erol; Lilla, Nadine (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Cutaneous angiosarcoma is a rare type of sarcoma with poor prognosis. Meningioma is the most frequent benign intracranial tumor. Despite the fact that meningiomas are mostly benign, bone and skin can be infiltrated. We report the rare case of an angiosarcoma on top of a meningioma with hyperostosis at exactly the same location mimicking a transosseous growth of a meningioma. An 84-year-old man presented with progressive swelling and ulcerous lesion of the forehead. The patient underwent surgery in an interdisciplinary setting together with a plastic surgeon, including resection of the intracranial tumor and infiltrated bone and skin. To the best of our knowledge, this is the only reported case of a meningioma and angiosarcoma in direct neighborhood. A preoperative biopsy of the skin tumor would have led initially to the correct diagnosis of an angiosarcoma and would have allowed a better planning of the operation and extent of resection.
Keywords: meningioma; cutaneous angiosarcoma; biopsy; bone infiltration; head